Multiple organ dysfunction syndrome pathogenesis and care: a complex systems' theory perspective - Papathanassoglou, Elizabeth; Bozas, Evangelos; Giannakopoulou, Margarita (My University, 2008)
Aims and objectives: To discuss multiple organ dysfunction syndrome (MODS) from a complex systems' theory perspective and to delineate a conceptual framework for the development and care of MODS. Background: MODS is an intricate and devastating manifestation of critical illness characterized by widespread aberrant molecular, cellular and systemic responses. Design and methods: Narrative literature review (MEDLINE, CINAHL databases) and knowledge synthesis with the theoretical assertions of chaos and complex systems' theory. Cellular and systemic response paradoxes in MODS (including cellular hypoxia, cell death and signalling) are reviewed. Results: The diseased person is depicted as a complex adaptive system. The relevancy of some of the principles of complex chaotic systems' theory to the proposed model is illustrated, including sensitive dependence on initial conditions, emergence, attractors, self-organization, self-organized criticality and emerging order. The transition from life-supporting to death-related organismic responses is illustrated as a critical event in MODS and care implications are drawn. Conclusions: Patient responses in MODS appear to conform to the principles of chaotic systems. Death is illustrated not as a consequence of homeostatic failure but as a 'deliberate' self-organized phenomenon entailing multiple dynamically evolving mechanisms. Relevance to clinical practice: Some of the principles of chaotic complex systems may need to be taken into account to advance care in MODS. An alternative theoretical perspective may support nurses to conceptualize both MODS and their role in a way that will help them to cope better with this devastating syndrome and develop practice.
Keywords: Complex adaptive systems; Chaos theory; Death; Nursing care; Strange attractor; Self-organization